Biological roles and potential applications of immune cell‐derived extracellular vesicles. Issue 1 (1st December 2017) - Wen, Chuan; Seeger, Robert C.; Fabbri, Muller; Wang, Larry; Wayne, Alan S.; Jong, Ambrose Y.
ABSTRACT: Extracellular vesicles (EVs) deliver bioactive macromolecules (i.e. proteins, lipids and nucleic acids) for intercellular communication in multicellular organisms. EVs are secreted by all cell types including immune cells. Immune cell‐derived EVs modulate diverse aspects of the immune system to either enhance or suppress immune activities. The extensive effects of immune cell‐derived EVs have become the focus of great interest for various nano‐biomedical applications, ranging from the medical use of nanoplatform‐based diagnostic agents to the development of therapeutic interventions as well as vaccine applications, and thus may be ideal for 'immune‐theranostic'. Here, we review the latest advances concerning the biological roles of immune cell‐derived EVs in innate and acquired immunity. The intercellular communication amongst immune cells through their EVs is highlighted, showing that all immune cell‐derived EVs have their unique function(s) in immunity through intricate interaction(s). Natural‐killer (NK) cell‐derived EVs, for example, contain potent cytotoxic proteins and induce apoptosis to targeted cancer cells. On the other hand, cancer cell‐derived EVs bearing NK ligands may evade immune surveillance and responses. Finally, we discuss possible medical uses for the immune cell‐derived EVs as a tool for immune‐theranostic: as diagnostic biomarkers, for use in therapeutic interventions and for vaccination.